2006
DOI: 10.1088/0953-8984/18/13/013
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from classical to relaxor ferroelectrics in BaTi1−xHfxO3ceramics

Abstract: In this paper we report the successful preparation of hafnium substituted barium titanate, i.e. BaTi1−xHfxO3 (BHT) ceramics with (x = 0.05,0.1,0.2,0.3 and 0.4). X-ray diffraction measurements followed by Reitveld analysis show the single-phase nature of these ceramics undergoing a tetragonal to cubic phase transformation for x≥0.10. Temperature dependent dielectric properties (ε′ and ε′′) of these single-phase BHT ceramics have been studied in the temperature range 90–375 K and frequency range 0.1–100 kHz. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…It can be seen from Figure that T C decreased by ~16°C from BCTZ20(T) to BCTZ50(O) and by ~41°C from BCTZ50(O) to BCTZ80(R), which implies a normal–to–relaxor ferroelectric crossover. Several studies have revealed that such a sharp decline should be observed in areas that demonstrate intermediate states between ferroelectric and relaxor behaviors . The diffuseness of the paraelectric to ferroelectric transition can be evaluated using the modified Curie‐Weiss law as follows: 1εr1εrm=)(TTεnormalmγC,where γ and C are assumed to be constant and γ is between 1 and 2, and T εm is temperature where the maximum dielectric constant ε rm .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen from Figure that T C decreased by ~16°C from BCTZ20(T) to BCTZ50(O) and by ~41°C from BCTZ50(O) to BCTZ80(R), which implies a normal–to–relaxor ferroelectric crossover. Several studies have revealed that such a sharp decline should be observed in areas that demonstrate intermediate states between ferroelectric and relaxor behaviors . The diffuseness of the paraelectric to ferroelectric transition can be evaluated using the modified Curie‐Weiss law as follows: 1εr1εrm=)(TTεnormalmγC,where γ and C are assumed to be constant and γ is between 1 and 2, and T εm is temperature where the maximum dielectric constant ε rm .…”
Section: Resultsmentioning
confidence: 99%
“…Note that the letter in parenthesis following the composition indicates the crystal structure. This is probably the pinching phase transition of the three phase transitions (C–T, T–O, and O–R), which is often observed when the Ti site of BaTiO 3 is substituted by ions such as Zr, Sr, Ce, and Hf . For Ba(Ti, Zr)O 3 , the three phase transitions (C–T, T–O, and O–R) began to overlap with increasing Zr content, and finally the strong increase and broadening of the dielectric anomaly was maximized at a Zr content of ~0.10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first set, we directly used the as crushed powders, but for the second one, the crushed powders were first annealed in high purity ͑99.99%͒ oxygen atmosphere at 950°C for 24 h. The two sets of the pelletized ceramics were then sintered at 1350°C for 12 h. The final sintered samples were subjected to x-ray diffraction ͑XRD͒, transmission electron microscopy ͑TEM͒, and temperature dependent dielectric characterizations. 11 Details of TEM and the dielectric measurement are given elsewhere. 8,11 All the pellets were found to be similarly dense, ϳ95% of their corresponding x-ray density.…”
mentioning
confidence: 99%
“…11 Details of TEM and the dielectric measurement are given elsewhere. 8,11 All the pellets were found to be similarly dense, ϳ95% of their corresponding x-ray density. Figure 1͑a͒ shows the XRD data of oxygenated SCT ceramics, which were Rietveld refined using space groups a͒ Author to whom correspondence should be addressed.…”
mentioning
confidence: 99%